The role of body image in sexual satisfaction among partnered older adults: a population-based study in four European countries - Kvalem, Ingela Lundin (2019)
Body image issues can affect all domains of sexual functioning. The aim of this study was to examine how, in a sociocultural context where physical and sexual attractiveness is equated with young and slim body ideals, appearance dissatisfaction and importance are related to sexual satisfaction in older adults in four European countries. A cross-sectional survey with probability samples of the population aged 60–75 years was used. Only respondents with a partner were included in this paper, and the countries included Norway (n = 957), Denmark (n = 846), Belgium (n = 612), and Portugal (n = 367). Sexual satisfaction, appearance dissatisfaction, and importance were assessed, and frequency of intercourse/kissing and cuddling, relationship satisfaction, age, and body mass index were all used as control variables. Belgian men scored significantly lower on sexual satisfaction, while there was no difference in sexual satisfaction in women. Appearance dissatisfaction was lower in Scandinavian women and men, and in Belgian men, and appearance salience was lower in Norwegian men and women, and in Portuguese women. Linear regression analysis revealed that, adjusting for confounders, appearance dissatisfaction was significantly related to sexual satisfaction in Scandinavian women and men, as well as in Belgian men. Compared to research on younger adults, appearance evaluation appeared to play an equally important role in sexual satisfaction in older adults in our study. The variation in appearance dissatisfaction in older adults across European countries is a novel finding that needs to be examined further.